Observation and quantification of pathological lesions in the musculoskeletal structures of the cervical spine - Roshier, Amanda Louise (2005)
This thesis describes the study carried out for the `Observation and Quantification of Pathological Lesions in the Musculoskeletal Structures of the Cervical Spine'. In particular, this study has focused on the identification and quantification of pathological lesions of the musculoskeletal complex of the cervical spine, resulting from a whiplash injury.